Piezo1 promotes vibration-induced vascular smooth muscle injury by regulating the NF-κB/p65 axis - Yingshan Zeng; Zhiquan Wu; Mengtian Xiong; Zhishan Liang; Ziyu Chen; Huimin Huang; Hongyu Yang; Qingsong Chen (Communications Biology)
Abstract Vibration induced damage to the peripheral circulatory system is thought to be an early stage of hand-arm vibration syndrome (HAVS) caused by occupational exposure to hand-transmitted vibration (HTV). This study investigated the mechanisms underlying vibration-induced vascular injury, focusing on the role of Piezo1, a mechanosensitive channel, and its association with the NF-κB/p65 signaling pathway. We demonstrated that vibration exposure leads to Piezo1-mediated upregulation of angiogenic chemokines, including CCL2, CCL5, CXCL1, CXCL2, and CXCL10, through the NF-κB/p65 pathway. To mimic the effects of vibration, a rat vibration model and a cellular vibration model were used. Animal and cellular models showed that vibration-induced vascular dysfunction while increasing Piezo1 expression. Piezo1 knockdown or p65 inhibition attenuated these effects, suggesting a crucial role for the Piezo1-NF-κB/p65 axis in vascular dysfunction. Furthermore, chemokines were identified as potential biomarkers for early diagnosis of HAVS in occupationally exposed individuals. These results highlight Piezo1 and the NF-κB/p65 pathway as potential therapeutic targets for HAVS and underscore the need for further validation in human samples and exploration of additional signaling mechanisms involved in vibration-induced vascular injury.